Differential Trial-Type Effects in an Implicit Relational Assessment Procedure: Extending the DAARRE Model. - de Almeida, Rodrigo Vianna; Barnes-Holmes, Dermot; Leslie, Julian C. (Psychological Record, 2024)
The differential arbitrarily applicable relational responding effects (DAARRE) model explains two effects commonly observed with the implicit relational assessment procedure (IRAP): the single trial-type dominance effect (STTDE) and the dissonant-target trial-type effect (DTTTE). We sought to explore variables that modulate these effects. Forty-two participants who completed an IRAP met the practice criteria (median latency ≤ 2,000 ms and accuracy ≥ 80% correct) and thus proceeded to six test blocks of trials. The IRAP had four trial-types: trial-type 1: happy-face—happy-word; trial-type 2: happy-face—fear-word; trial-type 3: fear-face—happy-word; trial-type 4: fear-face—fear-word. Participants were randomly assigned to start with a consistent (respond True, False, False, True, respectively, to the four trial-types) or inconsistent (opposite responding) block. Difference (D) scores were calculated (inconsistent minus consistent latencies). A significantly larger D score was observed in trial-type 2 relative to trial-type 3 (a DTTTE), but only for participants who started with the inconsistent block. A "happiness superiority" STTDE (i.e., larger D score on trial-type 1 relative to trial-type 4) was observed, but only for participants who failed to maintain the criteria at the trial-type level (in any of the trial-types). Overall, the findings highlight the importance of distinguishing between the functional versus relational properties of the stimuli presented within an IRAP. The modulation of the DTTTE is interpreted in terms of functional coherence between the target and response option in inconsistent blocks. A novel data-analytic algorithm is presented to identify performance criteria violations at the trial-type level. The findings suggest that a greater focus is required in relational frame theory on the impact of the functional properties of stimuli on relational framing.